2018
DOI: 10.5350/btdmjb.20170322030251
|View full text |Cite
|
Sign up to set email alerts
|

Examination of psychometric characteristics of the nursing image scale among nurse manegers

Abstract: Amaç: Bu çalışmanın amacı Tzeng tarafından hemşirelere yönelik kalıp yargıları temel alarak geliştirilen hemşirelik imaj ölçeğini Türkçeye uyarlamak ve psikometrik özelliklerini test etmektir.Yöntem: Çalışma dokuz farklı hastanede çalışan 194 yönetici hemşire ile gerçekleştirilmiştir. Ölçeğin Türkçeye uyarlamasında çeviri-geri çeviri yöntemi kullanılmıştır. Verilerinin değerlendirilmesinde sayı, yüzde, dil geçerliği, kapsam geçerliği (uzman görüşü, Kendall uyuşum katsayısı), açıklayıcı ve doğrulayıcı faktör an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Hemşirelik imajı, devamlı gelişim gösteren bir kavram olarak hemşirelerin iş performansını, işten ayrılma niyetini de etkilemektedir. Bu nedenle, imaj konusunda çalışmalar yapılması önemlidir (11)(12)(13) . Farklı dönemler ve önemli toplumsal olayların hemşirelik imajına etkisinin değerlendirildiği çalışmalar, konuyla ilgili bilgi birikimini de zenginleştirmektedir.…”
Section: Discussionunclassified
“…Hemşirelik imajı, devamlı gelişim gösteren bir kavram olarak hemşirelerin iş performansını, işten ayrılma niyetini de etkilemektedir. Bu nedenle, imaj konusunda çalışmalar yapılması önemlidir (11)(12)(13) . Farklı dönemler ve önemli toplumsal olayların hemşirelik imajına etkisinin değerlendirildiği çalışmalar, konuyla ilgili bilgi birikimini de zenginleştirmektedir.…”
Section: Discussionunclassified
“…Nursing image affects nurses' job performance, intention to quit, and professional development. Therefore, nursing image has always been considered an important concept in nursing (Kartal & Kantek, 2018). Many factors—such as school curriculum, educators, clinical practice environment, mentor nurses, and peers—contribute to the professional development of nursing students (Safadi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a strong and positive professional image among nursing students is important for their professional development and commitment (Dost & Bahçecik, 2015). Nursing image has always been considered an important concept in nursing (Kartal & Kantek, 2018) and there are studies in the literature that define the nursing image and influencing factors of students (Elibol & Harmancı Seren, 2017; Kim & Kwon, 2018; Yılmaz, 2019). In the studies, the students' perceptions of nursing image showed low (Elibol & Harmancı Seren, 2017) or above average in other words positive (Kim & Kwon, 2018; Yılmaz, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The image of nursing is a factor affecting nurses' work performance, their intention to leave the job, and nurses' status, strength, and skills in developing healthcare (Fletcher 2007;Takase, Maude & Manias 2006). Accordingly, the image of nursing has always been of great importance and concern (Emeghebo 2012; Kartal & Kantek 2018). Nurses considering the profession as promising and providing services to the society who are concerned with what the profession is could be more effective in modifying the negative perceptions of society regarding the profession.…”
Section: Introductionmentioning
confidence: 99%
“…2017). A positive image for nursing is critical in increasing nurses' job satisfaction as well as demonstrating professional successes and effectiveness (Hung et al 2019;Kartal & Kantek 2018). Thus, studies are required to investigate the professional image perceptions of nursing students as future nurses.…”
Section: Introductionmentioning
confidence: 99%